Photodynamic Therapy Mediated by 5-Aminolevulinic Acid Suppresses Gliomas Growth by Decreasing the Microvessels - 易伟 徐海涛 田道锋 吴立权 张申起 王龙 冀保卫 朱晓楠 Humphrey Okechi 刘刚 陈谦学 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
Although 5-aminolevulinic acid（5-ALA）-mediated photodynamic therapy（PDT） has been demonstrated to be a novel and effective therapeutic modality for some human malignancies, its effect and mechanism on glioma are still controversial. Previous studies have reported that 5-ALA-PDT induced necrosis of C6 rat glioma cells in vitro. The aim of this study was to further investigate the effect and mechanism of 5-ALA-PDT on C6 gliomas implanted in rats in vivo. Twenty-four rats bearing similar size of subcutaneously implanted C6 rat glioma were randomly divided into 3 groups： receiving 5-ALA-PDT（group A）, laser irradiation（group B）, and mock procedures but without any treatment（group C）, respectively. The growth, histology, microvessel density（MVD）, and apoptosis of the grafts in each group were determined after the treatments. As compared with groups B and C, the volume of tumor grafts was significantly reduced（P〈0.05）, MVD was significantly decreased（P〈0.001）, and the cellular necrosis was obviously increased in group A. There was no significant difference in apoptosis among the three groups. The in vivo studies confirmed that 5-ALA-PDT may be an effective treatment for gliomas by inhibiting the tumor growth. The mechanism underlying may involve increasing the cellular necrosis but not inducing the cellular apoptosis, which may result from the destruction of the tumor microvessels.